The usefulness of sport science in football & rugby league - Nash, D.; Martindale, R. (7th World Congress on Science and Football (WCSF), 2011, 2011)
Introduction Sport science research into various areas, e.g. strength & conditioning, psychology, motor skill acquisition, has generated vast quantities of information for sport coaches (Bishop, 2008; Reid et al., 2004; Williams et al., 2007). The aim of this study was to determine how helpful sport coaches within football and rugby league found this plethora of information. Methods Six groups of coaches were interviewed in focus groups, three from both football and rugby league. Each group consisted of 5-7 coaches, at novice, developmental or elite level in their respective sport. The semi-structured interviews lasted between 60 and 80 minutes, were digitally recorded and transcribed verbatim. The data was inductively analyzed to interpret the meaning of the phrases used by coaches in response to questions as well as the discussion arising from the group interviews (Côté et al., 1995). Results & Discussion The analysis revealed 206 raw data themes that were developed into 3 distinct themes: language; practical application and ease of access. There were key differences between both sport and level of coaching. Developmental rugby league coaches and elite football coaches had least use for sport science research whereas novice rugby league and developmental football coaches were enthusiastic and motivated to use in practical coaching sessions. Similar to many of the coaches in this study, Spinks (1997) drew attention to differences between the focus of sports science research projects and what coaches ``think`` they need to know to be better coaches. The elite football coaches, in particular valued experience and practical knowledge acquired from participation in sport and from other coaches above knowledge gained from sports science research (Quinlan, 2002). There was also considerable debate within all of the groups as to what sports science actually was, some individuals favouring inclusive definitions whereas others stuck to very rigid criteria. Conclusion Results from this study implied that sport coaches within football and rugby league do not find sport science research to be as useful as other sources of information. There is a suggestion that more recently qualified coaches are more open to this type of information.